2022
DOI: 10.1371/journal.pone.0262477
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions at the HIV-1 transframe region significantly impair virus infectivity

Abstract: A transframe region within HIV-1 Gag-Pol (referred to as p6* or p6pol), directly linked to the protease (PR) N-terminus, plays a pivotal role in modulating PR activation. To identify specific p6* residues involved in PR activation, we created a series of p6* mutants by making substitutions for conserved p6* residues. Our results indicate that some p6* mutants were defective in terms of virus infectivity, despite displaying a wild-type virus particle processing pattern. Mutations at p6* F8 reduced virus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, Yu et al [ 111 ] demonstrated that point mutations at highly conserved residues, specifically at position F8 in the transframe p6 region of Gag–Pol, result in insufficient viral processing due to impaired protease and reverse transcriptase activity.…”
Section: P6mentioning
confidence: 99%
“…Interestingly, Yu et al [ 111 ] demonstrated that point mutations at highly conserved residues, specifically at position F8 in the transframe p6 region of Gag–Pol, result in insufficient viral processing due to impaired protease and reverse transcriptase activity.…”
Section: P6mentioning
confidence: 99%